Ecosystem fragmentation drives increased diet variation in an endemic livebearing fish of the Bahamas - Araujo, Marcio S. [UNESP]; Langerhans, R. Brian; Giery, Sean T.; Layman, Craig A. (Wiley-Blackwell, 2014)
One consequence of human-driven habitat degradation in general, and habitat fragmentation in particular, is loss of biodiversity. An often-underappreciated aspect of habitat fragmentation relates to changes in the ecology of species that persist in altered habitats. In Bahamian wetlands, ecosystem fragmentation causes disruption of hydrological connectivity between inland fragmented wetlands and adjacent marine areas, with the consequent loss of marine piscivores from fragmented sections. We took advantage of this environmental gradient to investigate effects of ecosystem fragmentation on patterns of resource use in the livebearing fish Gambusia hubbsi (Family Poeciliidae), using both population- and individual-level perspectives. We show that fragmentation-induced release from predation led to increased G. hubbsi population densities, which consequently led to lower mean growth rates, likely as a result of higher intraspecific competition for food. This was accompanied by a broadening of dietary niches via increased interindividual diet variation, suggesting a negative effect of predation and a positive effect of intraspecific competition on the degree of diet variation in natural populations. Our results therefore indicate that habitat fragmentation can greatly impact the ecology of resilient populations, with potentially important ecological and evolutionary implications.
Keywords: Bahamas mosquitofish; food webs; individual specialization; niche variation; predation; RNA/DNA ratios; stable isotopes